EFFECT OF TEMPERATURE, HUMIDITY AND IRRADIANCE ON SOLAR POWER GENERATION (Journal of Engineering Studies and Research, 2021)
This paper studies the effect of temperature, humidity and irradiance on the power generated by a photovoltaic solar cell. This was achieved using pyranometer for determining the solar radiation, wet and dry thermometer for measuring humidity, and digital multimeter for voltage and current measurement. The result of the study show that power generation increases with increase of solar irradiance. Additionally, changes of humidity level and temperature do not significantly affect solar power generation. Furthermore, it was also observed that high temperatures and higher humidity levels accelerate the corrosion process on the solar cells which reduces the efficiency of the cells.
Keywords: solar irradiance, humidity, power generation, monocrystalline cells, temperature